Biosynthesis of Random-Homo Block Copolymer Poly[Glycolate-ran-3-Hydroxybutyrate (3HB)]-b-Poly(3HB) Using Sequence-Regulating Chimeric Polyhydroxyalkanoate Synthase in Escherichia coli - Arai, Shuzo; Sakakibara, Sayaka; Mareschal, Robin; Ooi, Toshihiko; Zinn, Manfred; Matsumoto, Ken’ichiro (Frontiers in Bioengineering and Biotechnology, 2020)
Glycolate (GL)-containing polyhydroxyalkanoate (PHA) was synthesized in Escherichia coli expressing the engineered chimeric PHA synthase PhaCAR and coenzyme A transferase. The cells produced poly[GL-co-3-hydroxybutyrate (3HB)] with the supplementation of GL and 3HB, thus demonstrating that PhaCAR is the first known class I PHA synthase that is capable of incorporating GL units. The triad sequence analysis using 1H nuclear magnetic resonance indicated that the obtained polymer was composed of two distinct regions, a P(GL-ran-3HB) random segment and P(3HB) homopolymer segment. The random segment was estimated to contain a 71 mol% GL molar ratio, which was much greater than the value (15 mol%) previously achieved by using PhaC1PsSTQK. Differential scanning calorimetry analysis of the polymer films supported the presence of random copolymer and homopolymer phases. The solvent fractionation of the polymer indicated the presence of a covalent linkage between these segments. Therefore, it was concluded that PhaCAR synthesized a novel random-homo block copolymer, P(GL-ran-3HB)-b-P(3HB).